Hospital practitioner views on the benefits of continence education and best ways to provide training. Issue 5 (12th January 2023) - Percival, John; Abbott, Katharine; Allain, Theresa; Bradley, Rachel; Cramp, Fiona; Donovan, Jenny; McCabe, Candy; Neubauer, Kyra; Redwood, Sabi; Cotterill, Nikki
Abstract: Aim: The aim of the study was to explore practitioners' experiences and perspectives on continence training, in order to understand its relevance to practice and how take‐up of, and engagement with, such training may be improved. Design: 27 qualitative interviews were conducted with nursing, medical and allied health practitioners in three hospitals. Methods: We analysed data thematically, both manually and with the aid of NVivo software. The research adheres to the consolidated criteria for reporting qualitative research checklist. Results: Practitioners asserted the likely benefits of evidence‐based continence training, including more judicious use of products, reduction in associated infection, better patient skin care and more facilitative communication with patients. Practitioners also identified preferred methods of continence training, according to their role and workload. To ensure better take‐up of, and engagement with, continence training, it must be authorized as essential and provided in ways that reflect professional preferences and pragmatic resource considerations.